2009
DOI: 10.1016/j.biocon.2009.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Available soil phosphorus in semi-natural grasslands: Assessment methods and community tolerances

Abstract: (2009). Available soil phosphorus in semi-natural grasslands: assessment methods and community tolerances. Biological Conservation, 142 (5) To test which methods are most suitable for measuring available P in soils of mesotrophic 20 grasslands, a bioassay experiment was undertaken to compare seven extraction methods with 21 the growth and P uptake of grassland species. Five species were grown together on a soil treated 22 to create a range of conditions of pH, mycorrhizal infection and P availability. 23 24 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
68
0
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 22 publications
4
68
0
9
Order By: Relevance
“…A higher carbon content leads to a higher heating [20,21,29]. In our study higher nitrogen fertilization means higher carbon content in the first and second year of reed canary grass swards use (Table 2).…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…A higher carbon content leads to a higher heating [20,21,29]. In our study higher nitrogen fertilization means higher carbon content in the first and second year of reed canary grass swards use (Table 2).…”
Section: Resultssupporting
confidence: 50%
“…The carbon content of biomass is around 45%, while coal contains 60% or greater [21]. A higher carbon content leads to a higher heating [20,21,29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the intrinsically low N levels in Patagonian soils (Diehl et al 2003), a small difference in N availability could have a considerable effect on the productivity of the system and consequently on the species richness. It has also been shown that low P availability is a prerequisite for high diversity (Critchley et al 2002;Gilbert et al 2009;Janssens et al 1998;McCrea et al 2004;McCrea et al 2001). An essential difference between the N and P soil cycles is that the available forms of N are easily lost from the system by leaching, fires, and denitrification, while P is bound to the soil.…”
Section: Introductionmentioning
confidence: 93%